2007
DOI: 10.1152/ajpcell.00194.2006
|View full text |Cite|
|
Sign up to set email alerts
|

Human NADH:ubiquinone oxidoreductase deficiency: radical changes in mitochondrial morphology?

Abstract: function of NADH:ubiquinone oxidoreductase or complex I (CI), the first and largest complex of the mitochondrial oxidative phosphorylation system, has been implicated in a wide variety of human disorders. To demonstrate a quantitative relationship between CI amount and activity and mitochondrial shape and cellular reactive oxygen species (ROS) levels, we recently combined native electrophoresis and confocal and video microscopy of dermal fibroblasts of healthy control subjects and children with isolated CI def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 76 publications
(76 reference statements)
6
118
0
1
Order By: Relevance
“…As complex I is the major site of physiological and pathological ROS production, 46,47 we inferred that decreased complex I activity enhanced ROS production, which in turn induced mitochondrial fragmentation or other morphology distortion as seen in the present study.…”
Section: Figsupporting
confidence: 72%
“…As complex I is the major site of physiological and pathological ROS production, 46,47 we inferred that decreased complex I activity enhanced ROS production, which in turn induced mitochondrial fragmentation or other morphology distortion as seen in the present study.…”
Section: Figsupporting
confidence: 72%
“…Mitochondrial network fragmentation has been mainly described in complex I and complex III-deficient cells (Pham et al, 2004;Benard et al, 2007;Koopman et al, 2007;Moran et al, 2010a).…”
Section: In Mitochondrial Disordersmentioning
confidence: 99%
“…A number of studies revealed no significant mitochondrial fragmentation in RC-deficient cells, which included fibroblast harboring mutations in complex I subunits, even in stressful metabolic conditions (Hanson et al, 2002;Guillery et al, 2008;Moran et al 2010b), and only in some cell lines a decreased rate of mitochondrial tubules formation after treatment with protonophores was detected (Guillery et al, 2008;Moran et al, 2010b). Some authors have suggested that the lowest complex I residual activity in fibroblasts could be associated with the highest ROS levels, and thus to more pronounced mitochondrial morphology alterations (Koopman et al, 2007). However, in many cases a straightforward relationship between decreased RC activities, increased ROS levels, and mitochondrial fragmentation cannot be established.…”
Section: In Mitochondrial Disordersmentioning
confidence: 99%
“…Mitochondria vary in number from cell to cell, are highly prone to oxidative damage, lack efficient mtDNA repair mechanisms, and can accrue mutations and go unnoticed [11][12][13]. Abnormal accumulation of defective mitochondria in cells can trigger activation of senescence or apoptosis [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%